The relationship of remnant cholesterol and abdominal obesity in children: A cross-sectional study - Tong, Jishuang; Li, Xinggui; Liang, Xiaoyue; Tang, Fang; Ren, Yanling; Hao, Guang; Peng, Xin; Luo, Sunqing; Feng, Ye; Huang, Daochao; Zhao, Li; Liang, Xiaohua (Frontiers in Cardiovascular Medicine, 2022)
Background Previous studies found that remnant cholesterol (RC) is a risk factor for cardiovascular diseases and childhood obesity is associated with cardiometabolic diseases. This study aimed to explore the relationship between RC and abdominal obesity in children. Methods A total of 5,959 children, aged 6−12 years old, were selected from a cross-sectional study in urban-rural areas of Chongqing, China. RC was calculated by total cholesterol (TC)—high-density lipoprotein (HDL-C) cholesterol—low-density lipoprotein (LDL-C) cholesterol and was divided into four groups by quartiles (Q1–Q4). Results Compared to children with the lowest RC (Q1), children with higher RC had significantly higher odds of abdominal obesity (Q2: OR = 1.450, 95% CI: 1.131−1.859, p < 0.05; Q3: OR = 2.127, 95% CI: 1.632−2.772, p < 0.001; Q4: OR = 2.386, 95% CI: 1.819−3.130, p < 0.001). In the stratified analyses by urban-rural areas, the odds ratios were greater in rural areas (Q2: OR = 2.228, 95% CI: 1.572−3.160, p < 0.001; Q3: OR = 3.668, 95% CI: 2.191−6.140, p < 0.001; Q4: OR = 6.490, 95% CI: 2.271−18.551, p < 0.001) than in urban areas (Q2: OR = 1.644, 95% CI: 1.192−2.266, p < 0.05; Q3: OR = 2.266, 95% CI: 1.667−3.082, p < 0.001; Q4: OR = 2.711, 95% CI: 2.005−3.665, p < 0.001). Conclusions Our study found that RC was positively correlated with abdominal obesity in children, and this association was higher for children living in rural areas.